Perspektif K.H. Imam Zarkasyi Mengenai Kesatuan Ilmu Pengetahuan - Rofiq, Ahmad Choirul (Institut Agama Islam Negeri (IAIN) Tulungagung, 2018)
The Islamic civilization in the era of classical Islamput science in a high position. At that time scholars did not distinguish between religious science and general science. But the principle of unity of knowledge then has faded and become a dichotomy of science when the Islamic civilization has declined. That fact is what stirs the anxiety of K.H. Imam Zarkasyi to affirm the principle of unity of knowledge because science is a unity which is derived from Allah. According to K.H. Imam Zarkasyi, the rise of Muslim civilization is very dependent on the management of educational institution quality and solidity of Muslims. Efforts to modernize education are absolutely necessary to produce pious and knowledgeable graduates. Therefore, education curriculum at Pondok Modern Gontor applies of religious lessons and of general lessons. It is the consistency of this educational institution that is finally able to realize the implementation of advanced Islamic education which contributes to the revival of Islamic civilization.